Sensitivity Analysis and Control in an Elastic CAD-Free Framework for Multi-Model Configurations - Mohammadi, Bijan (European Journal of Computational Mechanics, 2000)
This paper presents the extension of our CAD-Free plateform to the simulation and sensitivity analysis for design and control of multi-model configurations. The CAD-Free plateform has been enriched by an elastic model. We present the different ingredients of the plate form and discuss various coupling and control strategies. The targeted configurations gather some unstable aerodynamical behaviour.